Meningkatkan Mutu Belajar Fiqih melalui Model CTL Berbasis Canva: Studi Efektivitas di Madrasah Tsanawiyah - Al Ghozali, M. Dzikrul Hakim; Azizah, Nur Mita Riski (Lembaga Yasin AlSys, 2025)
The learning process in fiqh subjects at MTs Sunan Gunung Jati Jombang still relies on conventional models, and the integration of digital media remains suboptimal, leading to less-than-optimal student learning outcomes. This study aims to analyze the effectiveness of the Canva-based Contextual Teaching and Learning (CTL) model in enhancing the quality of fiqh learning. The research employs a pre-experimental design with a one-group pretest-posttest approach, where a single group undergoes both pre-test and post-test assessments. The sample consists of 20 students selected through a saturated sampling technique. Data collection methods include tests/questionnaires, observation, and documentation, with data analysis conducted using IBM SPSS Statistics Software. The results of the N-Gain test indicate that the effectiveness of the Canva-based CTL model is 57.536%, which falls within the